Contents of Training High-Graded Specialists in Informational Computer Technologies within the Context of Cognitive Processes (Using Programming as an Example) (Journal of Information Technologies in Education (ITE), 2008)
The original graphic method of the activity object’s cognitive structure formalization and the logic of its formation is represented.